(untitled) (المجلة الدولية للبحوث العلمية, 2024)
The goal of this study is to gather a High Strength Concrete (HSC) composite reinforced with silica fume and superplasticizers. Specimens are Cured by water and tested after aging for 3, 7, and 28 days, which are basic components of the High Strength Concrete (HSC) composites. After designing mix proportions, according to design requirements, some adjustments were made. Both fresh and hardened properties of the specimens were tested under standard conditions (curing schemes, setting time, etc.). Split strength test results were gathered and compared with the requirements.